Algoritms for pH control - Niemi, A. J.; Jutila, P. k. (Revista Técnica da Faculdade de Engenharia da de Zulia)
The acidity of solutions containing both weak and strong constituents simultaneously are discussed and algorithms for their control by feedback and feedforward are suggested.